All the gear: The prevalence and perceived effectiveness of recovery strategies used by triathletes - Leabeater, A. J.; James, L. P.; Huynh, M.; Vleck, V.; Plews, D. J.; Driller, M. W. (Performance Enhancement & Health, 2022)
Background: To minimise the deleterious effects of fatigue and muscle soreness and maintain availability for training and competition, triathletes may implement recovery strategies that act on various physiological, biomechanical, neurological or psychological domains. However, the use of common recovery strategies is yet to be investigated in this population. Methods: 322 triathletes (109 female, 212 male) of varying competition levels from 39 countries participated in the current study. Participants completed an anonymous online survey to determine their use and perceived effectiveness of various recovery strategies. Multiple chi-square tests were conducted to examine the association between training week type (normal vs post-competition), preferred event distance (short or long course), competition level and use of recovery strategies. Results: The most frequently used recovery strategies during normal training weeks were active recovery (51%), stretching (47%) and additional sleep (32%), while foam rolling (35%), massage guns (20%) and compression garments (19%) were the most commonly used recovery devices. The use of active recovery, additional sleep and professional massage was significantly (p = <.002) more common in the week following a competitive event than during a normal training week. Long course triathletes were more likely to use intermittent pneumatic compression (IPC) devices (p = .008) and hydrotherapy (p = .05) than were short-course triathletes. Conclusion: Active recovery, additional sleep and stretching are the preferred recovery choices for triathletes of all levels, though the use of foam rolling, massage guns and compression garments is common in this population. Active recovery, additional sleep and professional massage are more frequently used by triathletes in the week following a competitive event and are perceived to be the most effective recovery strategies overall.